Real-time monitoring of biomolecular interactions in blood plasma using a surface plasmon resonance biosensor - Špringer, Tomáš; Piliarik, Marek; Homola, Jiří (Analytical and bioanalytical chemistry, 2010)
We report a novel approach to biosensor-based observations of biomolecular interactions which enables real-time monitoring of biomolecular interactions in complex media. This approach is demonstrated by investigating the interaction between the human chorionic gonadotropin (hCG) and its antibody in blood plasma using a surface plasmon resonance biosensor and a dispersionless microfluidics system. The real-time binding data obtained in blood plasma are compared with those obtained in buffer and blood plasma using a conventional method. It is also demonstrated that the proposed approach can enhance the capability of the biosensor to detect biomolecules in complex samples in terms of detection time and sensitivity. In the model experiment, this approach is shown to enable direct detection of hCG in blood plasma at levels which are five times lower than those detected using the conventional detection approach.
Keywords: choriogonadotropin; povrchová plasmonová rezonance; biosenzitivní techniky; Biosensing Techniques; Humans; Microfluidics; Antibodies; mikrofluidika; Chorionic Gonadotropin; protilátky; lidé; Surface Plasmon Resonance